Effect of Sintering Temperature on Structural and Surface Morphology of Manganite: Pr0.75Na0.25-xAgxMnO3 - Teoh, Wilson; Suhadir Shamsuddin (Enhanced Knowledge in Sciences and Technology, 2022)
Monovalent doped Pr0.75Na0.2Ag0.05MnO3 manganite had been investigated to elucidate the effect of sintering temperature on the structural, surface morphology, density as well as porosity of perovskite manganite. The manganite samples were prepared with Pr2O3, Na2CO3, Ag2O and MnO2 powders of high purity using solid state reaction method. The structural characterisation was made using X-ray diffraction (XRD) and scanning electron microscope (SEM) equipped with energy dispersion x-ray spectroscopy (EDX) to investigate the surface morphology imaging and elemental composition analysis. The determination of density was done with the application of Archimedes Principle and the calculation of porosity was made using the standard formula. XRD analysis showed all samples were crystallized in an orthorhombic structure of Pnma space group with a decrease in unit cell volume as sintering temperature increase. SEM imaging of Pr0.75Na0.2Ag0.05MnO3 compound revealed an improvement on grain size, grain density and boundaries as well as the reduction of porosity with the increase in sintering temperature. The increase in bulk density and the decrease in porosity as sintering temperature rises were also confirmed through calculation using the lattice parameter of the samples analysed by XRD. The samples were shown to have the same composition without any impurities through EDX analysis. Hence, the correlation between XRD and SEM can be observed with the results from both analyses equipment showing a good agreement.